STUDY ON PIT CLOSURE GUIDELINES FOR OIL AND GAS PRODUCTION ACTIVITIES - R. Desrina; Evita H. Legowo; M. Mulyono (Scientific Contributions Oil and Gas, 2002)
Study on pit closure guidelines for the oil and gas industries has been conducted by Lemigas Team to observe the existing guidelines in the implementation of the guidelines in the closure program of the temporary use of pits. Goals of the study are to review the manual guideline or standard operating procedure (SOP) of pit closure applied to the petroleum fields, and compare it to the relevant government regulation. So far, governmental regulation concerning pit construction and closure has not been established yet. Nevertheless, management approach of pir construction and closure can be established by referring to the available regulation, namely PP. 18/1999- hazardous waste regulation, and the related Ministerial Decree. This approach is based on the reason that such solid wastes are also categorized as hazardous wastes. Looking at from regulation point of view, it can be said that pit management guideline established by the industry has fulfilled and matched with the available regulation such as Kep.-04/Bapedal/09/1995. Nevertheless, some criteria have to be re-evaluated and post-closure plan seem not to be included in the guidelines vet. This paper presents the results of the study describing the existing guidelines used by the oil and gas industry and its implementation as well as reviewing the government regulation related to the pit closure program.